Fragment Binding to Kinase Hinge: If Charge Distribution and Local pKa Shifts Mislead Popular Bioisosterism Concepts. Issue 1 (29th October 2020) - Oebbeke, Matthias; Siefker, Christof; Wagner, Björn; Heine, Andreas; Klebe, Gerhard
Abstract: Medicinal‐chemistry optimization follows strategies replacing functional groups and attaching larger substituents at a promising lead scaffold. Well‐established bioisosterism rules are considered, however, it is difficult to estimate whether the introduced modifications really match the required properties at a binding site. The electron density distribution and p K a values are modulated influencing protonation states and bioavailability. Considering the adjacent H‐bond donor/acceptor pattern of the hinge binding motif in a kinase, we studied by crystallography a set of fragments to map the required interaction pattern. Unexpectedly, benzoic acid and benzamidine, decorated with the correct substituents, are totally bioisosteric just as carboxamide and phenolic OH. A mono‐dentate pyridine nitrogen out‐performs bi‐dentate functionalities. The importance of correctly designing p K a values of attached functional groups by additional substituents at the parent scaffold is rendered prominent. Abstract : Designed with the correct p K a value and appropriate electron withdrawing and pushing groups, benzoic acid and benzamidine are bioisosteric with respect to the binding to the hinge region of a kinase.